AN ANALYSIS OF ERRORS BY THE THIRD YEAR STUDENTS AT SMPN 14 PEKANBARU IN WRITING DESCRIPTIVE TEXTS - Indah Khairunnisya; Eliwarti Eliwarti; Mahdum Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The objective of this research is to find out types of errors made by the third year students of SMPN 14 Pekanbaru in writing descriptive text. This is a descriptive research. The subject of this study was the third year students of SMPN 14 Pekanbaru. In conducting this research, the writer used 30 students as a sample. The students were selected to be the sample using cluster sampling technique. The instrument used to collect the data was writing test. The result of this research showed that the students committed error into four types: omission, addition, misformaion, and misordering. From the frequency of each error type, ‘omission’ was the error which most frequently produced by the students. It took 47,25% of the total errors. Moreover, 32,11% errors fell into error of ‘misformation’ and 14,68% errors fell into ‘addition’; whereas, for error of ‘misordering’, it only took 5,96%.Key Words: Error, Writing, Descriptive text.